Melatonin Reverses the Warburg-Type Metabolism and Reduces Mitochondrial Membrane Potential of Ovarian Cancer Cells Independent of MT1 Receptor Activation - Cucielo, Maira Smaniotto [UNESP]; Cesário, Roberta Carvalho [UNESP]; Silveira, Henrique Spaulonci [UNESP]; Gaiotte, Letícia Barbosa [UNESP]; Santos, Sérgio Alexandre Alcantara dos [UNESP]; Zuccari, Debora Aparecida Pires de Campos; Seiva, Fábio Rodrigues Ferreira; Reiter, Russel J.; Chuffa, Luiz Gustavo de Almeida [UNESP] (MDPI, 2022)
Ovarian cancer (OC) is the most lethal gynecologic malignancy, and melatonin has shown various antitumor properties. Herein, we investigated the influence of melatonin therapy on energy metabolism and mitochondrial integrity in SKOV-3 cells and tested whether its effects depended on MT1 receptor activation. SKOV-3 cells were exposed to different melatonin concentrations, and experimental groups were divided as to the presence of MT1 receptors (melatonin groups) or receptor absence by RNAi silencing (siRNA MT1+melatonin). Intracellular melatonin levels increased after treatment with melatonin independent of the MT1. The mitochondrial membrane potential of SKOV-3 cells decreased in the group treated with the highest melatonin concentration. Melatonin reduced cellular glucose consumption, while MT1 knockdown increased its consumption. Interconversion of lactate to pyruvate increased after treatment with melatonin and was remarkable in siRNA MT1 groups. Moreover, lactate dehydrogenase activity decreased with melatonin and increased after MT1 silencing at all concentrations. The UCSC XenaBrowser tool showed a positive correlation between the human ASMTL gene and the ATP synthase genes, succinate dehydrogenase gene (SDHD), and pyruvate dehydrogenase genes (PDHA and PDHB). We conclude that melatonin changes the glycolytic phenotype and mitochondrial integrity of SKOV-3 cells independent of the MT1 receptor, thus decreasing the survival advantage of OC cells.
Keywords: glucose; melatonin; mitochondrial metabolism; ovarian cancer; SKOV-3 cells; Warburg effect